2020
DOI: 10.1038/s41416-020-0989-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between adjuvant chemotherapy and survival in patients with rectal cancer and pathological complete response after neoadjuvant chemoradiotherapy and resection

Abstract: Background For patients with locally advanced rectal cancer (LARC), it is unclear whether neoadjuvant chemoradiotherapy-induced pathologic complete response (pCR) individuals would further benefit from adjuvant chemotherapy (ACT). Methods The pCR individuals who received different ACT cycles were paired by propensity score matching. Overall survival (OS), disease-free survival (DFS), local recurrence-free survival (LRFS), and distant metastasis-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“… 13 But several prospective studies indicated that ACT is unnecessary for NACRT-induced pCR LARC patients. 14 , 30 , 31 Agreeing with their study, patients with or without ACT had comparable OS rates and DMFS rates in our data. In stratified groups, patients with cT 3-4 , cN + and high risks to DM had no obvious benefit from ACT.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“… 13 But several prospective studies indicated that ACT is unnecessary for NACRT-induced pCR LARC patients. 14 , 30 , 31 Agreeing with their study, patients with or without ACT had comparable OS rates and DMFS rates in our data. In stratified groups, patients with cT 3-4 , cN + and high risks to DM had no obvious benefit from ACT.…”
Section: Discussionsupporting
confidence: 80%
“… 12 , 13 However, a multi-center retrospective study including 1041 LARC patients with pCR implied that similar OS, local recurrence-free survival (LRFS), distant metastasis-free survival (DMFS) and disease-free survival (DFS) were observed between the ACT group and the non-ACT group. 14 Obviously, the true value of ACT in pCR patients remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, there were some advantages and disadvantages. First, considering that the pCR patients were the main study objects in previous studies, 12 , 13 , 18 , 20 we also included ypT1–2N0 patients and our study participants also showed a good prognosis and, more importantly, were potential candidates for local excision selection. 9 Moreover, to the best of our knowledge, this was the largest‐scale study to analyze the correlation of clinicopathological characteristics including different nCT strategies and the intervals to surgery and good response; furthermore, we attained an answer as to whether ACT was necessary for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…8,11 Furthermore, among patients who downstaged to a pathological good response, the necessity of adjuvant chemotherapy treatment (ACT) was also deemed controversial. 5,7,[19][20][21][22] Several studies have reported that no survival benefits exist in concert with ACT among these good responders. 20,22 Nevertheless, other studies have shown that the delivery of ACT achieved an improvement in the DFS, thus supporting the necessity of ACT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation